Open or Closed? Elucidating the Correlation between Micropore Nature and Sodium Storage Mechanisms in Hard Carbon. Issue 11 (24th August 2022) - Surendran, Vishnu; Hema, Radhika Krishna; Hassan, Muhammed Shafeek Oliyantakath; Vijayan, Vinesh; Shaijumon, Manikoth M.
Abstract: The sodium storage mechanism related to a high voltage slope region and a low voltage plateau region observed commonly in hard carbon (HC) is still a topic of debate. The difference in physicochemical properties of controllably synthesized carbon reflects the ambiguity in explaining their charge storage mechanism. Herein, we attempt to unravel the sodium storage mechanism using HCs with controlled ′closed′ and ′open′ porosities. Opening the ′closed′ pores diminishes the plateau region but does not affect the slope region. Electrochemical measurements coupled with N2 and CO2 gas adsorption studies reveal a strong correlation between closed pores with a diameter ( d ), 0.4 < d <1.5 nm and capacity contribution from the plateau region, supporting the adsorption/intercalation‐pore filling model. Solid‐state NMR measurements confirm the near metallic state of sodium in the ′closed′ micropores of HCs at potentials close to 0 V ( vs . Na). Abstract : Sodium storage mechanism in hard carbon anodes is unveiled using samples with controllable open and closed pores that reveals strong correlation between plateau capacity of the sample and closed pore micropore nature. The near‐metallic state of sodium in the nanopores of hard carbons at potentials close to 0 V (vs. Na) is confirmed via solid‐state NMR measurements, suggesting an adsorption/intercalation‐pore filling model. @tvmiiser @vvssurendran